América Latina en la transición demográfica, 1800-1980. - Pérez Brignoli, Héctor (Población y Salud en Mesoamérica, 2010)
This paper was presented in the V Latinamerican Conference of Population; celebrated in Mexico in 1993. Its main idea was the demographical transition in Latin American and the Caribean.